P 23. Individualized I-waves adapted TMS – Preliminary results. Issue 8 (August 2021) - Brich, L.; Schaff, F.; Gleich, B.; Heidsieck, A.; Mall, V.; Jung, N.
Abstract : Introduction. Synaptic plasticity is considered the neurophysiological correlate of learning processes in the human brain. It can be studied through transcranial magnetic stimulation (TMS). A TMS over the primary motor cortex (M1) generates descending volleys, so called I-waves (I1-I3). Their latencies can be detected with "short interval intracortical facilitation" (SICF). These latencies seem to play a pivotal role in the induction of synaptic plasticity. A paired pulse TMS, based on the defined (1.5 ms), as well as on the individual I-waves, lead to an increase in corticospinal excitability. The aim of this study was to investigate the effects of an individualized quadri-pulse theta burst stimulation (i-qTBS) with 4 bursts, based on each of the individual I1-I3- waves latencies for the first time. Methods. We studied the individual I-wave latencies through SICF in posterior-anterior (PA) and anterior-posterior (AP) current flow direction in the human M1-HAND of 12 healthy subjects (23-34 years, f=8). We used a newly engineered stimulator (MSB, Munich) to apply paired pulses with interstimulus interval of 0, 1 ms to 6 ms in steps from 0, 1 ms with a biphasic pulse configuration (pulse duration: 160 µs). The bursts of the qTBS consist of 4 pulses. We applied an (i)-qTBS adapted to the individual I-waves over the same hotspot (M1-HAND). Subsequently, the motor evoked potentials (MEP) and the resting motor threshold (RMT) were recorded over the period of one hour (post1-4). Results. The statistical analysis (rmANOVA) of the i-qTBS in PA direction did not show changes of the MEP-amplitude comparing the pre- to the 4 post-readings (F(4, 44) = 1.314, p = .280). The i-qTBS in AP direction also did not show any changes in MEP-amplitudes (F(4, 40) = .462, p = .763) over the course of an hour. Discussion. An i-qTBS adapted to the individual I-wave latencies did not result in any changes of corticospinal excitability. Possible reasons for this might be the high number (>200) of pre-stimuli due to the SICF, or extinction phenomena of different I1-/I3-effects. Further studies on individualized stimulation are necessary in order to analyse the neurophysiological mechanisms of the effects. This will enable a targeted individual therapeutical application of qTBS in a clinical context.